The Capacity Efficiency Of Production Machinery And Raw Material Supply Control : Production Process In "Galvanized Steel" Company, Bekasi City - Wartini, Wartini; Wibowo, Martino (Terbuka Journal of Economics and Business, 2023)
To produce a product that is of good quality with a smooth production process, it is necessary to establish a system of Machine Efficiency Capacity and Raw Material Supplies appropriately, this is intended to make it easier for companies to meet the required quantity of production and efficiency efficiently and certainly affect the smooth production. The purpose of this research is to find out and analyze the Effect of Capacity of Machine Efficiency in Production and Inventory Control of Raw Materials on the Smooth Production Process in Bekasi Branch "Galvanized Steel" Company. The type of research used is observation with a multiple linear regression analysis model with 32 samples. The regression test results show that 58.5%, the smoothness of the production process can be explained by the capacity of machine efficiency, and control of inventory of raw materials, while the remaining 41.5% is explained by other factors not examined in this study. F test results show that simultaneously the efficiency of production machinery and raw material inventory control have a significant effect on the smooth production process. The results of the t test show partially the capacity of machine efficiency has a significant effect on the smoothness of the production process while the control variables for raw material inventory have no significant effect on the smooth production process in the branch company "GALVANIZED STEEL" Bekasi